Engineering micromyocardium to delineate cellular and extracellular regulation of myocardial tissue contractility. Issue 9 (20th July 2017) - Ariyasinghe, Nethika R.; Reck, Caitlin H.; Viscio, Alyssa A.; Petersen, Andrew P.; Lyra-Leite, Davi M.; Cho, Nathan; McCain, Megan L.
Abstract : By engineering tunable myocardial microtissues, we established that matrix elasticity regulates contractility more strongly than matrix ligand and fibroblast : myocyte ratio. Abstract : Cardiovascular diseases are a leading cause of death, in part due to limitations of existing models of the myocardium. Myocardium consists of aligned, contractile cardiac myocytes interspersed with fibroblasts that synthesize extracellular matrix (ECM). The cellular demographics and biochemical and mechanical properties of the ECM remodel in many different cardiac diseases. However, the impact of diverse cellular and extracellular remodeling on the contractile output of the myocardium are poorly understood. To address this, we micropatterned 13 kPa and 90 kPa polyacrylamide gels with aligned squares of fibronectin (FN) or laminin (LN). We seeded gels with two concentrations of primary neonatal rat ventricular myocytes, which naturally contain fibroblasts. Cells assembled into aligned "μMyocardia" with fibroblast : myocyte ratios dependent on initial seeding concentration. Using traction force microscopy (TFM), we found that the peak systolic longitudinal cross-sectional force was similar across conditions, but the peak systolic work was significantly lower on 90 kPa gels. This indicates that ECM elasticity dominates over ECM ligand and cell demographics in regulating contractile output. Because our platform provides independent control over cell–cell and cell–matrix interactions, it has many applications for cardiac disease modeling.